Structural Prospects and Challenges for Bio Commodity Processes - Michael Narodoslawsky (Food Technology and Biotechnology, 2010)
The current discussion about dwindling reserves of crude oil, rising fuel prices, global warming and supply disruption of natural gas has renewed interest in the provision of bioenergy and bio-based commodity products. There is a growing consensus that the 21st century will see a profound change in the resource base for industry and society, with less emphasis on fossil coal, oil and gas and more emphasis on renewable resources. This new resource base may take the form either of direct solar energy like photovoltaics and thermal solar energy or indirect utilisation of solar energy via biomass. Such a change in the raw material base, however, entails a profound revolution in the structure of processes, technologies employed and the economical framework of industry and society. Renewable resources constitute 'limited infinity': although they may be provided for infinite time, their yield is limited. This paper explores the strategic challenges for society in general and process industry in particular, and indicates some methodological approaches to meet these challenges, exemplified in case studies about decentralised bioethanol production and decentralised multifunctional production centres. The paper shows that utilising renewable resources enlarges the process concept by including resource provision and logistics into the process design. It also highlights a new balance between economy and ecology of scale when resource provision and logistics are taken into account. Ecological process evaluation as analytical methods and process synthesis as design methods will gain increasing importance for process technology as the share of renewable resources is increased.